Healthy Eating Index‐2015 as a predictor of ulcerative colitis risk in a case–control cohort. Issue 12 (21st November 2019) - Rahmani, Jamal; Varkaneh, Hamed Kord; Ryan, Paul M.; Zarezadeh, Meysam; Rashvand, Samaneh; Clark, Cain; Day, Andrew S; Hekmatdoost, Azita
Abstract : Objective: There is compelling clinical evidence implicating certain dietary components in the development and clinical course of progression in ulcerative colitis (UC). This study aimed to assess whether any association exists between ulcerative colitis and scores on a healthy eating index. Methods: In this case‐control study patients with UC were recruited and assessed together with healthy controls. The participants completed a validated 168‐item food frequency questionnaire, the results of which were subsequently used to generate individual healthy eating index (HEI‐2015) scores. Results: Altogether 58 patients with UC and 123 healthy controls were recruited. After controlling for confounding factors, participants who were in the highest quartile of the HEI‐2015 had a 66% lower odds ratio (OR) of UC than the lowest quartile (OR = 0.34, 95% confidence interval 0.12‐0.96). Conclusion: HEI‐2015 was associated with UC in this cohort. Further elucidation of the role of key dietary elements is now warranted.